Auditory long latency event-related potentials in Alzheimer's disease and multi-infarct dementia. Issue 9 (September 1988) - Neshige, R; Barrett, G; Shibasaki, H
Abstract : An auditory discrimination paradigm was employed to elicit event-related brain potentials in 13 patients with Alzheimer's disease and 14 patients with multi-infarct dementia. The P300 latency was significantly prolonged in 12 patients with dementia compared with age-matched controls and showed a significant negative correlation with the score of Wechsler Adult Intelligence Scale (WAIS), especially with that of Digit Span subtest. There was no disease specificity. After physostigmine treatment, P300 latency decreased and WAIS score increased in 6 among 10 cases.